So we have to solve 5x + 7y = 10, -3x + 14y = -6 by substitution, and we do this by, you guessed it, substituting!

5x + 7y = 10 --We first have to get x = something, so we can substitute x to find y.

/5 /5 /5 --Divide everything by 5

x + 7/5y = 2

-7/5y -7/5y --Subtract 7/5y from both sides

x = -7/5y + 2

-3x + 14y = -6

-3(-7/5y + 2) + 14y = -6 --Substitute x in

21/5y -6 + 14y = -6

+6 +6

4 1/5y + 14y = 0

y = 0

5x + 7(0) = 10 --Now put in y to find x

5x = 10

x = 2

So y = 0 and x = 2.

Let's check it:

-3(2) + 14(0) = -6

-6 = -6 ✔